Estimating structural budget balances in developing Asia - Jo\~ao Tovar Jalles (Asian Development Bank (ADB), 2024)
This paper reviews the current discussions, methods, and practices surrounding the estimation of reasonable proxies for the underlying fiscal position, a useful anchor for fiscal policy. An empirical application to developing Asian economies is carried out. There is no one-size fits all type of approach and the sensitivity and discernment regarding specific economies are important in various stages. The choice of the filter to decompose trends from cycles matters. The way to adjust revenues and expenditures entering the cyclically adjusted balance also matters-choices regarding economy-specific vs. panel estimations or the use of static vs. time-varying approaches need to be made. To deal with one-off operations, a narrative-based approach can complement the suggested identification based on large changes in cyclically adjusted government capital transfers. A discussion of other important factors that can affect the estimates of structural balances such as asset and commodity prices is also provided.
Keywords: C33; E62; H30; H60; O53; 330; budget elasticity; time-varying estimation; trend-cycle decomposition; cyclically adjusted balances; one-off fiscal operations